Note from Éamonn Duggan written from the Fr. Mathew Hall during the Easter Rising, - Duggan, Éamonn, 1874-1936 (1916)
Duggan's note confirms that he is still safe, that some of his comrades amongst the Volunteers have been wounded during the fighting and that he will let the recipient know if it is safe to receive visitors. He signs his note E. Duggan; the recipient is unclear, however it may be his fiancée May Duggan.